Nutrition-modulated, subtype-specific risk factors for catheter-related bloodstream infections in hospitalized patients with intestinal failure - Zhu, Minyi; Liu, Sirui; Wu, Yi; Pan, Qin; Zhang, Yupeng; Maitiabula, Gulisudumu; Gao, Xuejin; Wang, Xinying (Frontiers in Nutrition, 2025)
Background and aimsParenteral nutrition is essential for patients with intestinal failure but predisposes them to catheter-related bloodstream infection, a serious complication threatening survival. Prior research emphasizes catheter management, while the role of parenteral nutrition delivery strategies—particularly energy proportion and nutrient composition—remains poorly understood. This study investigates catheter-related bloodstream infection risk factors, focusing on parenteral nutrition energy supply and formulation, and evaluates subtype-specific susceptibilities in hospitalized patients with intestinal failure.MethodsThis retrospective study analyzed 321 hospitalized patients with intestinal failure, encompassing 9,365 catheter-days. catheter-related bloodstream infection incidence was calculated per 1,000 catheter-days. Univariate and multivariate logistic regression and Cox proportional hazards regression identified independent risk factors. Stratified analyses identified subtype-specific risks, and hospital stay length and health economic outcomes were assessed.ResultsThe overall catheter-related bloodstream infection incidence was 7.048 per 1,000 catheter-days, significantly exceeding benchmarks. Key independent risk factors were parenteral nutrition calories > 60% of resting energy expenditure (OR = 3.808, HR = 2.055), lymphocytopenia (< 1 × 109/L; OR = 6.047), high calorie-to-nitrogen ratio (≥ 100 kcal/g N; OR = 2.118), neutropenia (< 1.5 × 109/L; HR = 2.573), and hypertension (OR = 4.981). Subtype-specific modulation was evident. Catheter-related bloodstream infection significantly prolonged hospitalization by nearly 2 weeks and increased inpatient costs.ConclusionOptimizing parenteral nutrition strategies, particularly by minimizing duration of high proportion of energy supply by parenteral nutrition through progressive enteral nutrition, is critical to reduce catheter-related bloodstream infection. Administering a low calorie-to-nitrogen ratio parenteral nutrition formula with immunonutrients is essential in unstable type I/II patients, while type III requires emphasis on blood pressure management. Universal multidrug-resistant pathogen vigilance is needed.